2011
DOI: 10.14412/2074-2711-2011-152
|View full text |Cite
|
Sign up to set email alerts
|

Use of cereton in neurological care

Abstract: Ю.А. Старчина

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 4 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The choline alfoscerate formulation Cereton has an extensive evidence base, and its effi cacy has been demonstrated in correcting cognitive and affective disorders [39,40]. In addition, studies using genetic testing and biomarker determination have shown it to have neuroprotective potential [39], such that Cereton can be confi dently recommend for the complex therapy of patients with CFS.…”
mentioning
confidence: 99%
“…The choline alfoscerate formulation Cereton has an extensive evidence base, and its effi cacy has been demonstrated in correcting cognitive and affective disorders [39,40]. In addition, studies using genetic testing and biomarker determination have shown it to have neuroprotective potential [39], such that Cereton can be confi dently recommend for the complex therapy of patients with CFS.…”
mentioning
confidence: 99%